Analytical methodology to measure periodontal bone morphometry following orthodontic tooth movement in mice. (6th January 2021) - Fleissig, Omer; Hazan-Molina, Hagai; Chaushu, Stella; Aizenbud, Dror; Klein, Yehuda; Zini, Avraham; Gabet, Yankel
Abstract: Introduction: Basic research in orthodontics is commonly conducted in rodents. However, experimental studies on orthodontic tooth movement (OTM) lack a standard method to examine OTM and periodontal changes. This study describes a unifying protocol for the analysis of OTM and associated bone microarchitectural changes in mice using microcomputed tomography (µCT). Methods: Mice (10 animals/group) were divided into control and OTM groups. OTM was generated by anchoring a nickel–titanium closed-coil spring to the upper incisors to pull the upper left first molar. A third group of TNFα  −/− mice was added since these are known to have slower OTM. Using µCT, we implemented and tested a number of methods to measure OTM distance and examine 3D bone morphometric parameters associated with OTM in mice. Results: In total, we tested five methods to measure the OTM distance in mice. The results indicated that measuring the intermolar diastema, and assessing tooth movement relative to the anterior root of the zygomatic arch, displayed the lowest standard deviation and enabled optimal detection of intergroup differences. We also developed two protocols for µCT analysis of the periradicular bone that yielded no false-positive results. Our results revealed that including the width of the periodontal ligament rather than excluding it from the region of interest in mice detected more statistically significant differences in the morphometric parameters between the OTM and control sides and between WT and TNFα  −/− mice despite more subtle differences. Conclusions: We, therefore, propose new guidelines for a standardized μCT-based method to analyse OTM and the extent of the periradicular bone structural changes in mice.